Soluções de EDO e simulações numéricas para dinâmica relativa colisional entre veículos operacionais e detritos espaciais - Santana, Jadiane de Jesus (2018)
Earth's operational orbiting satellites are very useful for space science because it has great features as these services enable research and space explorations for scientific, commercial, and military interests as well. However, the increasing flow of space activities has increased the amount of debris orbiting in the operating regions, thereby increasing the chances of collisions in those areas, and allowing immeasurable damages if the satellite remains in this collision orbit. In view of the large number of operational objects, the study of evasive maneuvers for space vehicles has been growing, and this one is important in face of the possibility of collisions, not only with a single debris but with clouds of space debris. The objective of the evasive maneuver is to avoid collision, but by keeping the vehicle in its orbit nominally. The history of the phenomenon, that is, how it evolves over time, is found when the differential equation that represents the phenomenon is solved. From the point of view of Physics and Mathematics, the more realistic the model, the more difficult is the solution of the differential equations representing the phenomenon. Thus, this work seeks to present the analytical and semi-analytical solutions for the equations describing the relative dynamics between two bodies subjected to gravitational force, Chohessy-Wiltshire equations, under the influence of forces: gravitational, atmospheric drag, chemical propulsion (exponential model and linear model), atmospheric drag plus chemical propulsion and plasma propulsion, and finally present their respective computational simulations. These simulations made it possible to show what happens to the operational satellites against a collision, for each specified model. With the contribution of the development of the atmospheric drag equation, with the drag coefficient varying.